2021
DOI: 10.3390/ma14081950
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sinorhizobium meliloti Exopolysaccharide on Adsorption and Aggregation in the Copper(II) Ions/Supporting Electrolyte/Kaolinite System

Abstract: To obtain insight into physicochemical interactions between Cu(II) ions, kaolinite, and exopolysaccharide (EPS) synthesized by Sinorhizobium meliloti Rm 1021 soil bacteria, an adsorption, electrokinetic, and aggregation study was performed in the selected systems. The obtained data showed that supporting electrolyte type affects both EPS and Cu(II) ions adsorption. For initial Cu(II) concentration 100 mg/L, 4.36 ± 0.25 mg/g (21.80 ± 1.00%) of the ions were adsorbed in 0.001 M NaCl and 3.76 ± 0.20 mg/g (18.80 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The valence forces through the exchange or sharing of electrons between adsorbate and adsorbent. Such a good fitting of experimental data to PSO was also observed during the study on lead(II), chromium(VI) and copper(II) adsorption on kaolinite [ 41 , 42 , 43 ], as well as copper(II) and silver(I) ions on biochar [ 44 , 45 ]. However, it must be emphasized that some researchers do not agree with these assumptions.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The valence forces through the exchange or sharing of electrons between adsorbate and adsorbent. Such a good fitting of experimental data to PSO was also observed during the study on lead(II), chromium(VI) and copper(II) adsorption on kaolinite [ 41 , 42 , 43 ], as well as copper(II) and silver(I) ions on biochar [ 44 , 45 ]. However, it must be emphasized that some researchers do not agree with these assumptions.…”
Section: Resultssupporting
confidence: 65%
“…Therefore, it can be assumed that Pb 2+ and Zn 2+ form monolayers on the Na-X and Na-X(C) surfaces and all adsorption sites are energetically equivalent [ 27 , 40 , 48 ]. A good fitting of experimental data to the Langmuir model was also observed for the systems: kaolinite-Pb 2+ , kaolinite-Cr(VI), kaolinite-Cu 2+ and activated biochar-Cu 2+ [ 41 , 42 , 43 , 45 ]. The obtained data also indicated that larger amounts of metal ions were adsorbed on the zeolite than on its carbon composite.…”
Section: Resultsmentioning
confidence: 59%
“…The efficiency ( E , %) of pesticide adsorption was calculated using the equation [ 30 ]: where: C A is the concentration of pesticide adsorbed on the solid surface (mg/L); C 0 is the initial pesticide concentration in the sample (mg/L).…”
Section: Methodsmentioning
confidence: 99%
“…[4], have been used successfully. Biochar amendments, green waste compost and triple superphosphate (TSP) as well as clay minerals, such as kaolinite [5], were applied to reduce the bioavailability of heavy metals in soils [6,7]. Another way to improve soil quality is zeolites, which have been successfully used as an additive for the composting of organic solid waste.…”
Section: Introductionmentioning
confidence: 99%